Studies of interface structures of W films grown on patterned and bare Si(100) by TEM - Atici, Y (Springer Verlag, 1997)
W films were grown onto patterned n(+)-Si(100) and bare Si(100) wafers by low pressure chemical vapour deposition (LPCVD) at 230-280 degrees C. The films were investigated by transmission electron microscopy (TEM). The cross-sectional TEM samples of W/Si(100) exhibited a fine scale interface roughness, which was attributed to the surface preparation. Irregular W plug structures were observed depending on the predeposition procedures. It was observed that an insufficient deposition of W films on the contact surface leads to the presence of aluminium around and underneath the plugs. This was observed by energy dispersive X-ray spectrometry (EDX). A study, using conventional electron diffraction, confirmed that no silicides formed at the interfaces of W-bare Si(100) wafers.
Keywords: Chemical Vapor-Deposition; Tungsten